Provably Data-Driven Projection Method for Quadratic Programming - Nguyen, Anh Tuan; Nguyen, Viet Anh (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Projection methods aim to reduce the dimensionality of the optimization instance, thereby improving the scalability of high-dimensional problems. Recently, Sakaue and Oki (2024) proposed a data-driven approach for linear programs (LPs), where the projection matrix is learned from observed problem instances drawn from an application-specific distribution of problems. We analyze the generalization guarantee for the data-driven projection matrix learning for convex quadratic programs (QPs). Unlike in LPs, the optimal solutions of convex QPs are not confined to the vertices of the feasible polyhedron, and this complicates the analysis of the optimal value function. To overcome this challenge, we demonstrate that the solutions of convex QPs can be localized within a feasible region corresponding to a special active set, utilizing Caratheodory’s theorem. Building on such observation, we propose the unrolled active set method, which models the computation of the optimal value as a Goldberg-Jerrum algorithm with bounded complexities, thereby establishing learning guarantees. We then extend our analysis further to other settings, including learning to match the optimal solution and an input-aware setting, where we learn to map QP problem instances to projection matrices.